Do the Conventions on the Law of the Sea and Biological Diversity adequately protect marine biota from anthropogenic underwater noise pollution?. Issue 1 (May 2020) - Dwyer, Guy; Orgill, Tristan
Abstract : Anthropogenic underwater noise pollution (AUNP) generated by, inter alia, commercial shipping, military exercises, the use of sonar and seismic surveys has increased dramatically since the early 1950s. This has caused or contributed to the death and suffering of marine biota. International and domestic law must adequately regulate AUNP in order for this transboundary and transjurisdictional form of pollution to be addressed. This article examines the two most comprehensive multilateral international conventions regulating the world's oceans and biodiversity – the Convention on the Law of the Sea and the Convention on Biological Diversity – to address the question of whether these two conventions adequately protect marine biota from AUNP. It is argued that the existing regimes established under these conventions are inadequate because they do not: sufficiently recognise AUNP as a form of pollution; provide comprehensive and binding direction as to practical measures to prevent, mitigate or eliminate AUNP; or provide adequate enforcement regimes. To remedy these inadequacies, this article concludes by outlining a number of non-exhaustive law reform recommendations.